Para uma tipologia da sintaxe conectiva em português - Fonseca, Maria do Céu (2020)
Connective syntax or attributive connective syntax – expression derived from the logical-semantic concepts of “connecting”, “predicate”, “attribution of a quality” – is a descriptive model of how different languages establish attribution in several types of verbal and nonverbal head sentences. This formal model, based on a distinction between connective syntax and nuclear syntax, is situated within the framework of the theoretical reflection of several researchers gathered around C. Clairis (Clairis et al. 2005) and affiliated to the functionalist tradition of André Martinet. It is on the theoretical proposals of these authors, already applied in different languages, that we have relied on to present the functioning of connective syntax in the Portuguese language. This paper is written in honor of Prof. Maria da Graça Castro Pinto. May the subject, even outside the mainstream of theoretical conceptions and editorial priorities, be of interest to the honored Professor, always attentive to the cognitive and linguistic processes of the act of reading and of the writing proficiency, of the oral performance and of the grammatical knowledge, both inside and outside the school, in lifelong learning.